The Implementation of Internal Quality Assurance Cycle in Private Senior High School - Istihana, Istihana; amiruddin, Amiruddin; Naim, Amin (Universitas Islam Negeri Raden Intan Lampung, 2022)
Through quality assurance, there is an effort to ensure that the education process is implemented based on the standard. Quality assurance is very essential so that education is can create qualified output. The implementation of Internal Quality Assurance System (SPMI) requires many resources which becomes a challenge for education institution in Indonesia. On the other hand, ensuring the quality of education according to stakeholders’ expectations is a form of responsibility to stakeholders. This study aimed to describe the implementation of the Internal Quality Assurance cycle in SMA Global Madani Bandar Lampung. The data were collected from interviews with several informants, and tested by using triangulation. SMA Global Madani Bandar Lampung implemented quality assurance cycle through the process of planning, implementation, monitoring and evaluation, and corrective action. The stages of the internal quality assurance cycle were carried out within the framework of PDCA cycle (Plan, Do, Check, and Act). The integration of the school’s vision into the internal quality assurance process at SMA Global Madani Bandar Lampung was done through a quality development program that was aligned with the vision of the school with the basis of Islamic values, intelligence, and dignity, according to the vision of SMA Global Madani, that is Smart and Dignified Muslim.